2021
DOI: 10.9734/mrji/2021/v31i130297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial activity and Genotoxic Potential of Capparis spinosa (L.) Plant Extracts

Abstract: Objective: The aims of this study were to evaluate the antimicrobial activity and the genotoxic effect of both ethanolic and aqueous extracts of stem and leaf of Capparis spinosa (C. spinosa) plant on Escherichia coli (E. coli) ATCC 25922, Staphylococcus aureus (S. aureus) ATCC 6538P, clinical isolate of Methicillin-resistant S. aureus (MRSA) and Klebsiella pneumoniae (K. pneumoniae) and Candida albicans (C. albicans) ATCC 90028. Materials and Methods: The antimicrobial activity was determined using micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…In any case, the DNA was damaged by the treatment concentrations in the larvae. Similar study made on microbes from the extract of Capparis spinosa showed a genotoxic effect which was confirmed through RAPD-PCR [33].…”
Section: Discussionsupporting
confidence: 76%
“…In any case, the DNA was damaged by the treatment concentrations in the larvae. Similar study made on microbes from the extract of Capparis spinosa showed a genotoxic effect which was confirmed through RAPD-PCR [33].…”
Section: Discussionsupporting
confidence: 76%
“…None of the organs was most active than the others toward the tested microorganisms (Gull et al, 2015). Similar results were described by Adwan and Omar, (2021), stem and leaf ethanol extracts exhibited MIC of 6.25-100 mg/ mL against relatively identical bacterial strains (Gull et al, 2015;Mickymaray and Al Aboody, 2019;Adwan and Omar, 2021). Similarly, the ethanol fruit extract of Caper featured strong antibacterial activity with MIC of 1.73 mg/mL against Listeria monocytogenes and 6.25 mg/mL against E. coli and Pseudomonas aeruginosa.…”
Section: Antimicrobial Activitysupporting
confidence: 70%
“…The ethanol flower extract was not as strong as the fruit extract against the same microorganisms disclosing MIC ranging from 10-15 mg/mL (Ennacerie et al, 2017;Hameed et al, 2021). Caper extract also showed differential antibacterial activity against Pasteurella multocida, K. pneumonia, Acinetobacter baumannii, Enterobacter aerogenes, and Proteus mirabilis with DZI values of 24.9, 36, 21, 26 and 27 mm, respectively (Gull et al, 2015;Mickymaray and Al Aboody, 2019;Adwan and Omar, 2021). From other perspectives, the copper nanoparticles prepared from the aqueous extract from the fruits showed significant antibacterial activity with MIC of 5-10 mg/mL against S. aureus PTCC1112, B. cereus PTCC1556, E. coli PTCC1330, and K. pneumoniae PTCC1053 (Ebrahimi et al, 2017).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Bark and leaves of Kasokal showed less activity on the tested bacterial methanol extract but had moderate activity against B. cereus Frankland & Frankland, B. megaterium de Bary, Sarcina lutea (Schroeter) Cohn, E. coli, S. aureus, S. paratyphi, S. typhi (Schroter) Warren & Scott, S. boydii, S. dysenteriae (Shiga) Castellani & Chalmers, V. mimicus Davis, V. parahemolyticus (Fujino) Sakazaki, Iwanami, & Fukumi, S. cerevacae and C. albicans (Robin) Berkhout [42], conversely Rana et al [43] found strong activity against S. aureus and S. typhi with very low cytotoxicity. Kasene bark and fruit showed strong activity against S. aureus, Enterococcus faecalis (Andrewes & Horder) Schleifer & Kilpper-Bolz, E. coli, Proteus vulgaris Hauser and C. albicans and molecular modeling showed that almitic acid, pyrogalol and isopropylisothiocyanate are antimicrobial compounds [44] and demonstrated genotoxin potential against E. coli [45]. The antimicrobial activity of these plants needs to be analyzed when combined and rarely hot extracted as in the production of Minyak Sumbawa.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%